Service Quality and Communication Mediating Services-cape Effects on Patient Experience in Pharmacy Installation - Ketut Yuliani Wijaya; Rokiah Kusumapradja; Muhammad Fachruddin Arrozi (International Forum of Researchers and Lecturers, 2026)
Patient experience reflects patient’s comprehensive perceptions of service quality, the physical environment, and communication with healthcare providers. This study was motivated by the need to foster positive patient experience in the Pharmacy Installation of Graha Sehat Hospital, Probolinggo through improvements in service quality, servicescape, and effective communication. The objective of this research was to analyze the effects of service quality and servicescape on patient experience, with effective communication serving as an intervening variable. A quantitative approach was employed using Structural Equation Modeling (SEM) with AMOS. A total of 180 outpatient pharmacy patients were selected through voluntary sampling, with the sample size determined based on Hair’s method. The findings indicate that service quality, servicescape, and effective communication simultaneously exert a positive and significant effect on patient experience. Partially, service quality has a positive and significant effect on patient experience, while servicescape does not have a direct significant effect on patient experience. Effective communication, however, demonstrates a positive and significant influence on patient experience. Furthermore, effective communication significantly mediates the relationship between servicescape and patient experience, but it does not mediate the relationship between service quality and patient experience. The managerial implications for hospital management highlight the need to strengthen service quality improvement strategies, optimize spatial layout and environmental comfort in the pharmacy setting, and establish concise communication standards that include essential medication counseling points. Such measures are necessary to ensure that communication quality remains consistent, even during peak patient volume periods with limited-service time.